Perceived impacts of climate change on rural poultry production: a case study in Limpopo Province, South Africa. (21st April 2022) - Nyoni, Njongenhle M. B.; Grab, Stefan; Archer, Emma; Hetem, Robyn
ABSTRACT: Rural farming households in developing countries frequently contend with multiple challenges, including a lack of resources, food insecurity, and poverty. Climate change threatens to compound existing challenges, particularly in such rural subsistence economies with limited adaptive capacity. We aim to establish farmers' perspectives on likely impacts of climate change on their rural poultry production in northern South Africa. A baseline questionnaire-based study was conducted across 106 households in the town of Musina, South Africa. Most households lacked reliable and adequate sources of income and had, for example, days when they had to skip meals as a coping strategy. With such poverty, coupled with poor access to scientific information on agricultural production, these farmers typically have limited capacity to adapt to shocks such as climate variability and change. Farmers reported a reduction in poultry productivity in recent years, coinciding with increased ambient temperatures. There are concerns that recent and ongoing warming trends will have negative impacts on the future growth and wellbeing of birds. However, the farmers in our study perceived their poultry as hardy and well adapted to survive any future climatic changes and may be uninclined to take adaptive action at this stage.